Es Krim Oat Milk Tinggi Serat dengan Penambahan Buah Naga - Tri Rettagung Diana; Aulia Faza (Garina, 2024)
. Ice cream product development is now increasingly preferred and varied, so ice cream is innovated into high-fibre ice cream that can be accepted by all people. The objectives of this research include: 1) Knowing the public acceptance of high-fibre ice cream with dragon fruit and oat milk, 2) Knowing the right composition of ingredients in high-fibre ice cream with dragon fruit and oat milk, 3) Knowing the nutritional content of high-fibre ice cream products with dragon fruit and oat milk. The research methods used included literature, experiments, documentation, sensory tests, and nutritional content tests. The first experiment was carried out using oatmeal and dragon fruit, because the results were unsatisfactory, the second experiment was carried out using Oat milk and dragon fruit, the results of the second experiment the texture of the ice cream was still unsatisfactory, so the third experiment was carried out by adding skim milk powder. Organoleptic test results obtained ice cream products with dragon fruit as much as 20% of the liquid is the most preferred product by panellists. The formula preferred by panellists in ice cream products is with oat milk 500g, dragon fruit 100g, stevia sugar 5.2g, ice cream stabiliser 2g, and skim milk powder 25g. The nutrient content per 100g of ice cream is 19.23% carbohydrate, 5.18% fat, 3.93% protein, 16.40% fibre